Agro-industry, exports, and income distribution: A multiplier decomposition analysis for Myanmar - Dirk van Seventer; Finn Tarp (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2020)
This paper considers the impacts of agro-industry development and international trade on income distribution in Myanmar, focusing on low-income rural households. We use a social accounting matrix multiplier (SAM) decomposition model featuring detailed economic linkages. After describing the Myanmar economy through the lens of a SAM for 2017, we focus on agriculture development. Our results suggest that low-income rural households benefit considerably from exogenous increases in crop and agro-processing activities. A full decomposition of the multipliers indicates that low-income rural farming households link strongly to agro-processing, mainly through spillover and feedback effects. However, agro-processing is at a low level of development in Myanmar. We then consider international trade, which reveals high rates of import leakages and that broad export improvement would benefit low-income rural farm households more than other households. This suggests that investment in agro-processing value chain development would be beneficial overall and particularly for low-income rural households.
Keywords: E16; O1; O2; O53; 330; social accounting matrix; decomposition; Myanmar